Utilization of municipal solid waste incineration fly ash with red mud-carbide slag for eco-friendly geopolymer preparation. (15th March 2022) - Bai, Yanying; Guo, Weichao; Wang, Xiaoliang; Pan, Huimin; Zhao, Qingxin; Wang, Dongli
Abstract: Municipal solid waste incineration fly ash (MSWIFA), as a hazardous solid waste, contains such toxic substances as heavy metals and dioxin, making its disposal a global public health concern. This study aims to comprehensively combine solid waste red mud (RM), carbide slag (CS), and MSWIFA into eco-friendly geopolymer. This experiment used CS slurry and RM slurry without drying and grinding, effectively reducing energy consumption and cost. The mechanical and environmental properties of geopolymer were characterized by strength, chloride ion curing rate, and leaching concentration of heavy metals. The microscopic hydration mechanism of the binder was investigated using XRD, FTIR, TG-DTG, SEM + EDS, and MIP tests. The results show that when RM: CS: MSWIFA = 5: 2: 3, the 28 d compressive strength can reach 11.7 MPa, the chloride ion curing rate is 80.41%, and leaching levels of toxic substances are lower than the limits for landfill disposal regulated by the China standard (GB16889-2008). The Al–O and Si–O chemical bonds in RM were broken in the alkaline environment provided by CS and MSWIFA, and formed hydrate calcium chloroaluminate (HCC) and C–S–H gel with calcium ions and chloride ions. These hydration products can fill pores and reduce porosity, making the pores in the structure mainly gel micropores and mesopores with volume fractions of 10.3 and 68.1% respectively. This study expands the application of a new waste alkaline activator in alkaline activation and provides methods for MSWIFA solidification. Graphical abstract: Image 1 Highlights: The synergistic use of CS and MSWIFA as alkaline activators outperformed single mixing. The highest compressive strength was obtained with a RM-to–CS–to-MSWIFA ratio of 5:2:3. C–S–H gel and HCC are the main hydration products, enhancing the pore structure. The new geopolymer has good ability to immobilize heavy metals and chloride ions.